Seminar and workshop reports - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
CD-ROM technology has become an important tool for storing and retrieving large quantities of information. This technology has great potential and already offers an excellent opportunity to respond to the information needs of scientists,...